Socio-demographic characteristics, nutritional status, and red meat intake on blood cholesterol level among staffs in Universiti Sains Malaysia, Kelantan - Xin, Khor Wei (Universiti Sains Malaysia, 2015)
In general, high blood cholesterol level is related with the risk of heart diseases. A cross-sectional study was carried out with the main objective of determine the factors associated with blood cholesterol level among staffs in Health Campus, Universiti Sains Malaysia. A total of hundred staffs were recruited in this study by using convenient sampling whereby three schools of USM in Health Campus were included. A questionnaire which includes socio-demographic characteristics, medical history, anthropometric indicators, biochemical indicators and red meat intake was used to survey the respondents and data were analyzed. The gender distribution for this study was 40 male and 60 female respondents. The age range for these respondents was from 23 to 59 years whereas the median age for these respondents was 35 years old. Blood cholesterol level was break into 2 categories which were healthy range (<5.2mmol/L) and slight risk/high risk range (>5.2mmol/L). Age group 18 to 39 years and age group 40 to 59 years had a total of 40.3% and 63.2% of slightly risk or high risk blood cholesterol respectively with the significant association between age group and blood cholesterol level (g^=4.916, p=0.027). Besides, normal BMI group had 66.7% of respondents achieved healthy blood cholesterol level whereas underweight, overweight and obese group had 39.7% achieved healthy blood cholesterol with the significant association between BMI and blood cholesterol level Furthermore, normal blood pressure group had 60.8% of respondent achieved